A sodium supplement, a sodium ion battery, an electronic device and a method for preparing a sodium supplement
By introducing a carbon material coating layer into the sodium replenisher and doping it with non-metallic and loaded metal atoms, the decomposition gas is captured, solving the problem of gas generation from sodium replenisher decomposition in sodium-ion batteries, thus improving sodium replenishment efficiency and battery life.
Patent Information
- Application Number
- CN202511695258.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2045-11-19
AI Technical Summary
Existing sodium replenishment agents generate gas when they decompose and release active sodium ions in sodium-ion batteries, leading to increased internal pressure and side reactions between the electrolyte and active materials, which affects battery life and sodium replenishment efficiency.
A sodium supplement agent is designed, comprising a core and a coating layer. The core is composed of sodium-supplementing material, and the coating layer is composed of carbon material, metal atoms, and non-metal atoms. By doping non-metal atoms and loading metal atoms in the carbon coating layer, the gas released during decomposition is captured, the decomposition potential is reduced, and the sodium supplementation efficiency is improved.
It effectively reduces the decomposition and gas production of sodium supplement, improves the sodium supplement efficiency and battery energy density, and extends battery cycle life.
Smart Images

Figure CN121172308B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and in particular to a sodium supplement, a sodium-ion battery, an electronic device, and a method for preparing the sodium supplement. Background Technology
[0002] Energy storage technology has developed rapidly in recent years, with lithium-ion batteries being the most representative. Lithium-ion batteries are characterized by long cycle life and high energy density, and are widely used in consumer electronics, new energy vehicles, and aerospace.
[0003] The rapid development of the lithium battery industry has also driven up the price of lithium salts, leading to a sharp increase in raw material costs. This has limited the further development and application of lithium-ion batteries. Sodium-ion batteries, due to their highly competitive cost advantages and sustainable resource supply, have attracted attention and are expected to become a substitute for lithium-ion batteries.
[0004] Sodium-ion batteries are generally characterized by low energy density and low initial coulombic efficiency due to inherent defects in the positive and negative electrode materials. To address these issues, sodium-ion batteries typically introduce a sodium-replenishing agent into the positive electrode to replenish active sodium ions. However, currently used sodium-replenishing agents generate gas during the decomposition and release of active sodium ions, increasing the internal pressure of the battery and raising the likelihood of oxidation side reactions in the electrolyte and active materials, thus affecting the battery's lifespan.
[0005] Therefore, it is necessary to design a sodium supplement, a sodium-ion battery, an electronic device, and a method for preparing the sodium supplement to improve the above-mentioned problems. Summary of the Invention
[0006] This invention provides a sodium replenishing agent, a sodium-ion battery, an electronic device, and a method for preparing the sodium replenishing agent, in order to improve the technical problems of low sodium replenishment efficiency and decomposition gas generation affecting battery life in sodium-ion batteries.
[0007] In a first aspect, the present invention provides a sodium supplement comprising a core and a coating layer.
[0008] The core comprises a sodium-supplementing material; the coating layer comprises a carbon material, metal atoms, and non-metal atoms, wherein the metal atoms and the non-metal atoms are located in the carbon material; the metal atoms include at least one of noble metal atoms and transition metal atoms.
[0009] In one example of the present invention, at least some of the non-metallic atoms are doped on the surface of the carbon material, and the metal atoms are loaded in the carbon material.
[0010] In one example of the present invention, the non-metallic atoms form hydrophilic groups on the surface of the carbon material.
[0011] In one example of the present invention, the core has a mass content of 85% to 96% in the sodium supplement, and the coating layer has a mass content of 4% to 15% in the sodium supplement.
[0012] In one example of the present invention, the mass content of the metal atoms in the coating layer is 0.1% to 1%.
[0013] In one example of the present invention, the mass content of the non-metallic atoms in the coating layer is 4% to 15%.
[0014] In one example of the present invention, the sodium supplement material includes at least one of Na2CO3, Na2NiO2, NaCrO2, Na2S, CH3COONa, Na2C4O4, and Na2C2O4.
[0015] In one example of the present invention, the carbon material includes at least one of graphene, carbon nanotubes, hard carbon, soft carbon, carbon fiber, and conductive carbon.
[0016] In one example of the present invention, the non-metallic atom includes at least one of N, B, S, and P.
[0017] In one example of the present invention, the noble metal atom includes at least one of Ir, Rh, Ru, and Pd.
[0018] In one example of the present invention, the transition metal atom includes at least one of Ni, Co, Mn, and Fe.
[0019] In a second aspect, the present invention also provides a method for preparing a sodium supplement, the method comprising:
[0020] Carbon materials are mixed with non-metallic raw materials and sintered to obtain a first modified material; the first modified material is a carbon material doped with non-metallic atoms.
[0021] The metal element raw material is mixed with the first modified material and sintered to obtain the second modified material; the second modified material is the first modified material loaded with metal atoms;
[0022] The sodium-supplementing material is mixed and ground with the second modified material to obtain a sodium-supplementing agent.
[0023] In a third aspect, the present invention also provides a sodium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises a positive current collector and a positive active material layer, and the positive active material layer comprises a sodium supplement agent as described in any of the preceding examples, or a sodium supplement agent prepared by the preparation method described in any of the preceding examples.
[0024] In a fourth aspect, the present invention also provides an electronic device comprising the sodium-ion battery described in any of the foregoing examples.
[0025] The sodium replenishing agent provided by this invention comprises a core and a coating layer. The core includes a sodium replenishing material, and the coating layer includes a carbon material containing metal atoms and non-metal atoms. In the sodium replenishing agent, the carbon coating layer surrounding the core promotes efficient electron transfer, reduces the decomposition potential of the sodium replenishing agent, and improves the sodium replenishment efficiency. Meanwhile, the non-metal atoms doped in the carbon coating layer and the metal atoms loaded in the carbon coating layer can capture the gases released during the decomposition of the sodium replenishing material, effectively reducing their own decomposition gas production and preventing side reactions between the released gases and the electrolyte and the sodium-intercalated negative electrode material. This ensures the sodium replenishing agent's effect on improving battery energy density and cycle life. Attached Figure Description
[0026] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application. It is obvious that the drawings described below are merely some embodiments of this application, and those skilled in the art can obtain other embodiments based on these drawings without inventive effort.
[0027] In the attached diagram:
[0028] Figure 1 This is a schematic diagram of the structure of the sodium supplement in one embodiment of the present invention;
[0029] Figure 2 This is a schematic flowchart of a sodium supplement preparation method in one embodiment of the present invention;
[0030] Figure 3 This is a SEM image of the sodium supplement in Example 7 of the present invention;
[0031] Figure 4 (a) to Figure 4 (d) is the EDS test chart of the sodium supplement in Example 7 of the present invention; wherein... Figure 4 (a) Shows the distribution area of Na element in the sodium supplement. Figure 4 (b) Shows the distribution area of O element in the sodium supplement. Figure 4 (c) Shows the distribution area of nitrogen element in sodium supplement. Figure 4 (d) shows the distribution area of Fe element in the sodium supplement.
[0032] The attached figures are labeled as follows:
[0033] 10. Core; 20. Coating layer; 21. Carbon material; 22. Non-metallic atom; 23. Metallic atom. Detailed Implementation
[0034] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. It should also be understood that the terminology used in the embodiments of the present invention is for describing specific implementation schemes and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers.
[0035] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" used in this specification are only for clarity of description and are not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered as part of the scope of the invention.
[0036] To address the low energy density of sodium-ion batteries, sodium-replenishing agents are typically introduced into the positive electrode to replenish active sodium ions after the initial charge, thus compensating for the lack of active sodium provided by the sodium-depleted positive electrode material and the loss of active sodium due to the formation of the SEI film on the surface of the negative electrode material. However, commonly used sodium-replenishing materials suffer from high decomposition potentials. When introduced into the battery, these materials are often incompatible with the electrolyte and fail to fully release active sodium ions during the initial charge, resulting in poor initial charge capacity and low sodium-replenishing efficiency. Furthermore, these commonly used sodium-replenishing materials generate gases during the decomposition and release of sodium ions. For example, Na₂CO₃, Na₂O₂, and Na₂O release active oxygen. These released gases increase the internal pressure of the battery and raise the risk of side reactions between the electrolyte and active materials.
[0037] To address the aforementioned issues, this application provides a sodium replenishing agent. This agent has a carbon coating layer surrounding its core. By incorporating metal and non-metal atoms into the carbon coating layer, the decomposition potential of the sodium replenishing agent is effectively reduced. Furthermore, during the decomposition of the sodium replenishing agent, the metal and non-metal atoms in the coating layer are used to capture the gas released by the sodium replenishing material. This reduces the negative impact of the sodium replenishing agent's gas production on the battery, ensuring that the sodium replenishing agent maintains its particle structure integrity after decomposition and sodium release, thus preventing the collapse of the positive electrode active material layer structure and affecting the battery's cycle life.
[0038] like Figure 1As shown, in a first aspect, this application provides a sodium supplement agent comprising a core 10 and a coating layer 20. The core 10 comprises a sodium-supplementing material, and the coating layer 20 covers the outside of the core 10. The coating layer 20 comprises carbon material 21, metal atoms 23, and non-metal atoms 22. The carbon material 21 serves as the main material of the coating layer 20, covering the outside of the core 10. The carbon material 21 is doped with non-metal atoms 22, which are connected to the carbon material 21 by chemical bonds. The carbon material 21 also contains single metal atoms 23.
[0039] In the sodium supplement, the type of sodium-supplementing material contained in the core 10 is not limited, and the core 10 may be selected from sodium-supplementing materials commonly used in the art. For example, in some embodiments, the sodium-supplementing material contained in the core 10 may be selected from at least one of Na2CO3, Na2NiO2, NaCrO2, Na2S, CH3COONa, Na2C4O4, and Na2C2O4. The sodium-supplementing material can be any one of the materials listed above, such as Na2CO3, Na2NiO2, NaCrO2, Na2S, CH3COONa, Na2C4O4, or Na2C2O4. The sodium-supplementing material can also be any combination of two or more of the materials listed above. For example, the sodium-supplementing material can be a combination of Na2CO3 and Na2O2, or a combination of Na2CO3 and Na2O, or a combination of Na2O2 and Na2O, or a combination of Na2CO3 and Na2NiO2, or a combination of NaCrO2 and Na2S, or a combination of CH3COONa and Na2C2O4, or a combination of Na2CO3, Na2O2, and CH3COONa, or a combination of Na2CO3, Na2O, and Na2C2O4, etc., and so on. When the sodium-supplementing material is a combination of two or more materials, the proportion of each material within the combination is not limited and can be mixed in any proportion. In other embodiments, the sodium-supplementing material can also be materials not listed above.
[0040] The commonly used sodium replenishing materials have excessively high decomposition potentials. This high decomposition potential prevents the replenishing material from fully releasing active sodium during the initial charging process, resulting in low replenishment efficiency. Furthermore, these materials with excessively high decomposition potentials are incompatible with the electrolyte, hindering effective sodium replenishment. In this application's sodium replenishing agent, the coating layer 20 outside the core 10, based on the high conductivity of the carbon material 21, effectively reduces the resistance to electron migration within the agent, promotes efficient electron transfer, accelerates the decomposition rate, lowers the decomposition potential, and thus improves the replenishment efficiency. Simultaneously, the coating layer 20 effectively reduces direct contact between the core 10 and the external environment, enhancing the stability of the sodium replenishing agent.
[0041] like Figure 1 , Figure 3 and Figure 4 As shown, the coating layer 20 contains non-metallic atoms 22 and metallic atoms 23, where the metallic atoms 23 include at least one of noble metal atoms and transition metal atoms. The metallic atoms 23 and non-metallic atoms 22 in the coating layer 20 work synergistically to effectively capture the gases released from the decomposition of the sodium supplement material, reduce the gas production from the decomposition of the sodium supplement, and improve the catalytic activity and conductivity of the sodium supplement, thereby further reducing the decomposition potential of the sodium supplement.
[0042] like Figure 1 As shown, in the coating layer 20, metal atoms 23 are supported in the carbon material 21 in the form of single atoms. Based on their unique electronic structure and quantum size effect, the single metal atoms 23 effectively enhance the catalytic activity of the sodium supplementer with a relatively low loading amount through high metal atom utilization, thereby improving the reaction kinetics of the sodium supplementer and reducing its decomposition potential. Furthermore, the metal atoms 23 supported in the carbon material 21, as a highly active catalyst, can achieve efficient adsorption of various molecules, thus effectively adsorbing the gas released by the sodium supplementer during decomposition and reducing the gas production during decomposition.
[0043] like Figure 1 As shown, in the coating layer 20, non-metallic atoms 22 are doped into the carbon material 21. The non-metallic atoms 22 are chemically bonded to the carbon material 21 to break the electronic symmetry of the carbon material 21 and introduce more active sites into the coating layer 20. The active sites introduced by the doping of non-metallic atoms 22 (such as pyridine nitrogen, graphitic nitrogen, thiophene sulfur, etc.), based on their own electron-deficient structure, can effectively adsorb the gas produced by the decomposition of sodium supplementation materials, including active oxygen. On the other hand, they can further promote the transfer of electrons in the sodium supplementation agent on the basis of the highly conductive carbon material 21, improve the decomposition ability of the sodium supplementation agent under low voltage, and reduce the decomposition potential of the sodium supplementation agent. In addition, non-metallic atoms 22 also help to anchor active metals, increase the loading and stability of metal atoms 23, and enhance the catalytic effect of metal atoms 23 on sodium supplementation materials and the adsorption effect on the gas produced by sodium supplementation materials.
[0044] Furthermore, although the carbon material 21 in the coating layer 20 can promote electron transfer in the sodium replenishing agent and reduce its decomposition potential, the hydrophobic properties of the carbon material 21 surface hinder the wetting of the sodium replenishing agent by the electrolyte. This makes it difficult for the lower ion conductivity of the sodium replenishing agent surface to match its higher electron conductivity, thereby exacerbating the polarization risk of the sodium replenishing agent and affecting its sodium replenishment efficiency. The sodium replenishing agent of this application forms porous structures and hydrophilic groups on the surface of the carbon material 21 by doping non-metallic atoms 22 into it. These include nitrogen doping introducing pyridine nitrogen, graphitic nitrogen, and quaternary nitrogen; phosphorus doping forming CPO, COP, and C3-P=O; and sulfur doping forming thiophene and SO42-SO ... y(0 < y < 6), etc. Hydrophilic groups introduced by doping non-metallic heteroatoms 22. The hydrophilic groups introduced on the carbon material 21 can improve the wettability of the coating layer 20 to the electrolyte, accelerate the extraction rate of sodium ions from the sodium supplement, inhibit the polarization of the sodium supplement during the decomposition process, and further improve the specific capacity of the sodium supplement.
[0045] Furthermore, carbon materials 21 doped with non-metallic atoms 22 also exhibit better mechanical properties. For example, boron-doped carbon nanotubes are harder, tougher, and have higher compressive strength than pure carbon nanotubes; sulfur-doped carbon nanotubes have good toughness and flexural modulus; and nitrogen-doped carbon nanotubes have high mechanical strength and heat resistance.
[0046] It should be noted that carbon materials 21 doped with metal atoms 23 and non-metal atoms 22 can be prepared by various methods, such as physical grinding and mixing, chemical vapor deposition, arc discharge, laser evaporation, etc.
[0047] In some embodiments, the mass content of the core 10 in the sodium supplement is any value in the range of 85% to 96%, for example, the mass content of the core 10 can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% or 96%.
[0048] In some embodiments, the mass content of the coating layer 20 in the sodium supplement is any value in the range of 4% to 15%, for example, the mass content of the coating layer 20 can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0049] It should be noted that the specific form of the carbon material 21 in the coating layer 20 is not limited and may include morphological carbon and amorphous carbon. In some embodiments, the carbon material 21 in the coating layer 20 may be selected from at least one of graphene, carbon nanotubes, hard carbon, soft carbon, carbon fiber, and conductive carbon. That is, the carbon material 21 can be any one of the materials listed above, such as graphene, carbon nanotubes, hard carbon, soft carbon, carbon fiber, or conductive carbon; the carbon material 21 may also be any combination of two or more of the materials listed above, for example, a combination of graphene and carbon nanotubes, or a combination of graphene and carbon fiber, or a combination of conductive carbon and carbon nanotubes, or a combination of hard carbon and conductive carbon, or a combination of graphene, carbon nanotubes, and conductive carbon, or a combination of hard carbon, graphene, and conductive carbon, etc., which will not be listed here. When the carbon material 21 is a combination of two or more materials, the proportion of each material within the combination is not limited and can be mixed in any proportion. In other embodiments, the carbon material 21 may also be a material not listed above.
[0050] In some embodiments, the mass content of metal atoms 23 in the coating layer 20 is any value within the range of 0.1% to 1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%. Based on its high atomic utilization, the metal atoms 23, when loaded in the coating layer 20 at the above-mentioned mass content range, can effectively improve the catalytic efficiency for the decomposition of sodium-supplementing materials without significantly affecting the energy density of the sodium-supplementing agent.
[0051] In some embodiments, the transition metal atom 23 is selected from at least one of Ni, Co, Mn, and Fe. That is, the transition metal atom can be any one of the materials listed above, such as Ni, Co, Mn, or Fe; the transition metal atom can also be any combination of two or more of the materials listed above, for example, a combination of Ni and Co, or a combination of Ni and Mn, or a combination of Mn and Fe, or a combination of Mn and Co, or a combination of Ni, Fe, and Co, or a combination of Ni, Co, Mn, and Fe, etc., and so on. When the transition metal atom is a combination of two or more materials, the proportion of each material within the combination is not limited, and they can be mixed in any proportion. In other embodiments, the transition metal atom can also be a material not listed above.
[0052] In some embodiments, the noble metal atom 23 is selected from at least one of Ir, Rh, Ru, and Pd. That is, the noble metal atom can be any one of the materials listed above, such as Ir, Rh, Ru, or Pd; the noble metal atom can also be any combination of two or more of the materials listed above, for example, a combination of Ir and Rh, or a combination of Ir and Ru, or a combination of Pd and Rh, or a combination of Pd and Ru, or a combination of Rh, Ru, and Pd, or a combination of Ir, Rh, Ru, and Pd, etc., and so on, without further listing. When the noble metal atom is a combination of two or more materials, the proportion of each material within the combination is not limited, and they can be mixed in any proportion. In other embodiments, the noble metal atom can also be a material not listed above.
[0053] In some embodiments, the mass content of non-metallic atoms 22 in the coating layer 20 is 4% to 15%, for example, it can be 4%, 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%. When the mass content of non-metallic atoms 22 in the coating layer 20 is within the above range, the improvement effect of non-metallic atom doping on the electronic conductivity and surface wettability of the sodium supplement can be ensured, and excessive doping can be avoided from causing excessive damage to the carbon layer, thereby affecting the protective effect of the coating layer 20 on the core 10.
[0054] In some embodiments, the non-metallic atom 22 includes at least one of N, B, S, and P. That is, the non-metallic atom 22 doped in the coating layer 20 can be any one of the materials listed above, such as N, B, S, or P; the non-metallic atom 22 doped in the coating layer 20 can also be any combination of two or more of the materials listed above, for example, the non-metallic atom 22 can be a combination of N and S, or a combination of N and P, or a combination of B and P, or a combination of S and B, or a combination of N, B, and P, or a combination of N, B, S, and P, etc., and will not be listed one by one here. When the non-metallic atom 22 is a combination of two or more materials, the proportion of each material in the combination is not limited, and they can be mixed in any proportion. In other embodiments, the non-metallic atom 22 can also be a material not listed above.
[0055] In a second aspect, the present invention also provides a method for preparing the sodium supplement in any of the above embodiments, such as... Figure 2 As shown, the preparation method of this sodium supplement includes the following steps:
[0056] S1. Carbon material is mixed with non-metallic element raw materials and sintered to obtain a first modified material; the first modified material is a carbon material doped with non-metallic atoms;
[0057] S2. The metal element raw material is mixed with the first modified material and sintered to obtain the second modified material; the second modified material is the first modified material loaded with metal atoms;
[0058] S3. Mix and grind the sodium-supplementing material with the second modified material to obtain a sodium-supplementing agent.
[0059] In step S1, carbon material is mixed with non-metallic element raw materials and sintered to dope non-metallic atoms into the carbon material, thereby obtaining a first modified material. For example, in one instance, carbon material and non-metallic element raw materials are mixed and ball-milled for 12 to 48 hours to obtain a mixed powder; then, under a protective atmosphere, the mixed powder is sintered at a temperature of 600°C to 1200°C for 4 to 6 hours to obtain a carbon material doped with non-metallic atoms.
[0060] In some embodiments, the carbon material is selected from at least one of graphene, carbon nanotubes, hard carbon, soft carbon, carbon fiber, and conductive carbon.
[0061] In some embodiments, the non-metallic element raw material is a precursor material containing a non-metallic element, which is at least one of N, B, S, and P. For example, the nitrogen source in the non-metallic element raw material can be selected from at least one of urea, polyacrylonitrile, melamine, or aminomethylphosphonic acid; the boron source in the non-metallic element raw material can be selected from at least one of boric acid, boron oxide, or sodium tetraborate; the sulfur source in the non-metallic element can be selected from at least one of sulfur powder, ferrous sulfate, or potassium sulfate; and the phosphorus source in the non-metallic element raw material can be selected from at least one of red phosphorus, sodium dihydrogen phosphate, or tripotassium phosphate.
[0062] In step S2, the first modified material is mixed and sintered with a metallic element raw material to obtain a first modified material loaded with single metal atoms. For example, in one example, the metallic element raw material and the first modified material are placed in a solvent at a preset mass ratio and stirred for 8 to 12 hours to obtain a mixed solution; then the mixed solution is centrifuged and dried to obtain a composite powder, which is a carbon material doped with non-metallic atoms containing the metallic element raw material; finally, under a protective atmosphere, the composite powder is sintered at a temperature of 600℃ to 1200℃ for 2 to 4 hours to obtain a second modified material, which is a carbon material loaded with metallic atoms and doped with non-metallic atoms.
[0063] In some embodiments, the metal element raw material is a precursor material containing a metal element, wherein the metal element is selected from at least one of noble metal elements and transition metal elements. Noble metal elements include at least one of Ir, Rh, Ru, and Pd, and transition metal elements include at least one of Ni, Co, Mn, and Fe. Specifically, the precursor material containing a noble metal element can be a noble metal halide, such as iridium trichloride, palladium chloride, rhodium trichloride, ruthenium chloride, etc.; the precursor material containing a transition metal element can be a transition metal salt, such as iron acetate, manganese acetate, nickel acetate, cobalt acetate, etc.
[0064] In step S3, the sodium-supplementing material and the second modified material are mixed according to a preset mass ratio, and then thoroughly ground to coat the core surface with the second modified material, thereby obtaining the sodium-supplementing agent. The mass ratio of the core material to the second modified material is (85~96):(4~15). For example, in one instance, the core material is first ball-milled for 12 to 24 hours to adjust the particle size to a preset range; then, the core material and the second modified material are mixed according to the preset mass ratio, and ball-milled for another 12 to 48 hours to obtain the sodium-supplementing agent.
[0065] In a third aspect, the present invention also provides a sodium-ion battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive and negative electrodes, and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive electrode material, a positive electrode conductive agent, a positive electrode binder, and a sodium supplement agent as described in any of the above embodiments, or a sodium supplement agent prepared by the preparation method described in any of the above embodiments. The negative electrode includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer includes a negative electrode material, a negative electrode conductive agent, a thickener, and a negative electrode binder. The positive and negative electrode materials can intercalate and deintercalate sodium ions to achieve energy storage and release. The electrolyte is the carrier for sodium ion transport between the positive and negative electrodes. The separator is permeable to sodium ions but non-conductive, thereby separating the positive and negative electrodes to prevent short circuits.
[0066] It should be noted that the preparation of the positive electrode, negative electrode, separator, electrolyte, and assembly of the electrochemical device in a sodium-ion battery can be carried out using conventional methods in this field. The following is an example description of the preparation method for a sodium-ion battery:
[0067] Preparation of positive electrode sheet: The positive electrode material, a composite material containing sodium supplement (the sodium supplement has a mass content of 0.5%~10% in the composite material), a positive electrode conductive agent, and a positive electrode binder are mixed in a weight ratio of (90~98):(1~4):(1~4), optionally 95:2.5:2.5. N-methylpyrrolidone (NMP) solvent is added, and the mixture is stirred under vacuum until the system is homogeneous and transparent to obtain a positive electrode slurry. This positive electrode slurry is uniformly coated onto a positive electrode current collector aluminum foil, which is then air-dried at room temperature and transferred to an oven for further drying. Finally, the foil is cold-pressed and slit to obtain the positive electrode sheet.
[0068] The cathode material includes sodium-containing compounds, specifically NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, and NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaMn2O4, NaNi 1 / 2Mn 3 / 2O2, NaFePO4, Na4Fe3(PO4)2P2O7 (NFPP for short), NaMnPO4, NaCoPO4, Na2FePO4F, Na2MnPO4F, Na2CoPO4F, Na3PS4, P2-Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 The cathode material can be one or at least two of the materials listed above, such as NaFeO2 or Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, or Na2FePO4F, etc.; or any combination of two or more of the materials listed above, such as a combination of NaFeO2 and NaCoO2, or a combination of NaCrO2, NaMnO2 and NaNiO2, or a combination of Na2FePO4F and Na2MnPO4F, or NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2 and Na 2 / 3 Fe 1 / 3 Mn 2 / 3 Compositions of O2, etc., will not be listed here. It should be noted that the positive electrode material can also be any positive electrode active material not listed above. When the positive material is a combination of two or more, there is no restriction on the ratio between the components in the composition, and they can be mixed in any proportion.
[0069] The positive electrode conductive agent can be selected from at least one of conductive materials such as carbon black (Super P), acetylene black, nano metal powder, carbon nanotubes (CNT), graphene, and carbon nanofibers (VGCF); the positive electrode binder can be selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), for example, PVDF can be selected as the positive electrode binder.
[0070] Negative electrode preparation: Negative electrode material, negative electrode conductive agent, negative electrode binder, and negative electrode dispersant are mixed in a mass ratio of (93~98):(0.2~1.5):(1~3):(0.01~1.5). N-methylpyrrolidone or deionized water is added as a solvent, and the mixture is thoroughly stirred under vacuum to obtain a negative electrode slurry. This negative electrode slurry is uniformly coated onto a negative electrode current collector, which is then air-dried at room temperature and transferred to an oven for further drying. Finally, the negative electrode is cold-pressed and slit to obtain the negative electrode sheet.
[0071] The negative electrode material can be hard carbon. The negative electrode conductive agent can be selected from at least one conductive material such as carbon black (Super P), acetylene black carbon nanotubes (CNT), nano-silver powder, graphene, and carbon nanofiber (VGCF). The negative electrode binder is selected from at least one binder such as polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), and styrene-butadiene rubber (SBR). The thickener is selected from carboxymethyl cellulose, which can be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).
[0072] Electrolyte preparation: In this application, the electrolyte can be any conventional type of electrolyte in the art. For example, in an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) are uniformly mixed at a volume ratio of 1:1 to obtain an organic solvent. Then, fluoroethylene carbonate (FEC) additives accounting for 5% of the mass fraction of ethylene carbonate (EC) and dimethyl carbonate (DMC) are added to the organic solvent. Next, fully dried sodium salt NaClO4 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0073] Membrane preparation: The membrane is selected from conventional porous polymer membranes in the art. For example, the membrane material can be selected from one or more combinations of polyvinylidene fluoride, polystyrene, polyarylether sulfone, polyvinyl chloride, polypropylene, polyethylene, polyamide, polyimide, polyacrylic acid, polyacetal, polycarbonate, polyester, polyetherimide, polyimide, polyketone, polyphenylene ether, polyphenylene sulfide, polymethylpentene, polysulfone nonwoven glass, glass fiber materials, ceramics, metal oxides, and composites of organic and inorganic substances. For example, in one instance, the diaphragm is a porous polyethylene (PE) or polypropylene (PP) membrane, optionally a PP / PE / PP porous membrane, with a thickness of 9 μm to 18 μm, such as 9 μm, 12 μm, 16 μm or 18 μm; an air permeability of 180 s / 100 mL to 380 s / 100 mL, such as 180 s / 100 mL, 280 s / 100 mL or 380 s / 100 mL; and a porosity of 30% to 50%, such as 30%, 40% or 50%.
[0074] Battery Assembly: Battery assembly is carried out according to conventional methods. For example, after preparation, the negative electrode, separator, and positive electrode are stacked in sequence and placed in an aluminum-plastic film to obtain a bare cell. The bare cell is then placed in a casing and thoroughly baked to ensure that its water content is below 450 ppm. The prepared electrolyte is injected into the dry cell and sealed. After formation, venting, and aging, a sodium-ion battery with the preset capacity is obtained.
[0075] The conditions for formation, venting, and aging are as follows: charging to the cutoff voltage at a rate of 0.1 to 0.33 C, venting vacuum of -40 to -98 kPa, and venting time of more than 10 seconds; aging temperature of 40 to 50 °C and aging time of 24 to 72 hours.
[0076] In a fourth aspect, the present invention also provides an electronic device comprising the sodium-ion battery described in any of the above embodiments. The sodium-ion battery can be used as a power source for the electronic device or as an energy storage unit for the electronic device. The electronic device can be a vehicle, mobile phone, portable device, laptop computer, ship, spacecraft, electric toy, and power tool, etc. Vehicles can be gasoline-powered vehicles, natural gas-powered vehicles, or new energy vehicles; new energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc.; spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc.; electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc.; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. The embodiments of this application do not impose special limitations on the above-described electronic devices.
[0077] The technical solution of the present invention will be described in detail below through several specific embodiments and comparative examples. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products or can be prepared by conventional methods in the art.
[0078] Example 1
[0079] This embodiment provides a sodium supplement agent comprising a core and a coating layer surrounding the core. The core contains 90% by mass and is made of Na2CO3. The coating layer contains 10% by mass and comprises carbon material, specifically carbon nanotubes. The carbon material is doped with non-metallic N atoms and loaded with metallic Pd atoms. The non-metallic N atoms in the coating layer contain 6% by mass and the metallic Pd atoms in the coating layer contain 0.2% by mass.
[0080] The preparation process of this sodium supplement is as follows:
[0081] (1) The carbon material and non-metallic element raw material urea are mixed evenly and ball milled for 24 hours after mixing to obtain mixed powder. Then the mixed powder is placed in a furnace and heated to 900°C at a rate of 5°C / min under a nitrogen atmosphere. The furnace environment is heated to 900°C for 5 hours and cooled to obtain the first modified material, which is a carbon material doped with N atoms.
[0082] (2) The first modified material and the metal element raw material palladium chloride were added to deionized water and stirred evenly to obtain a mixed solution; the mixed solution was centrifuged and dried to obtain a composite powder, which is the first modified material containing the metal element raw material; finally, the composite powder was placed in a furnace and heated to 1000°C at a rate of 5°C / min under a nitrogen atmosphere, and heated at 900°C for 3 hours. After cooling, the second modified material was obtained, which is the first modified material loaded with Pd atoms.
[0083] (3) Mix the core material and the second modified material according to a preset mass ratio, and ball mill for 24 hours to obtain the required sodium supplement.
[0084] Example 2
[0085] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that in step (1), the mass ratio of carbon material to non-metallic element raw material urea is controlled so that the mass content of N atoms in the coating layer of the sodium supplement is 4%.
[0086] Example 3
[0087] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that in step (1), the mass ratio of carbon material to non-metallic element raw material urea is controlled so that the mass content of N atoms in the coating layer of the sodium supplement is 15%.
[0088] Example 4
[0089] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that in step (2), the mass ratio of the first modified material to the metal element raw material palladium chloride is controlled so that the mass content of Pd atoms in the coating layer of the sodium supplement is 0.1%.
[0090] Example 5
[0091] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that in step (1), the mass ratio of carbon material to non-metallic element raw material urea is controlled so that the mass content of N atoms in the coating layer of the sodium supplement is 15%; in step (2), the mass ratio of the first modified material to metallic element raw material palladium chloride is controlled so that the mass content of Pd atoms in the coating layer of the sodium supplement is 1%.
[0092] Example 6
[0093] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that the metal atoms loaded in the coating layer of the sodium supplement are Ir. In step (2), by controlling the mass ratio of the first modified material to the metal element raw material iridium trichloride, the mass content of Ir atoms in the coating layer of the sodium supplement is 0.1%.
[0094] Example 7
[0095] This embodiment provides a sodium supplement with the same system as in Example 1. The difference between this embodiment and Example 1 is that the metal atoms loaded in the coating layer of the sodium supplement are Fe. In step (2), by controlling the mass ratio of the first modified material to the metal element raw material ferric acetate, the mass content of Fe atoms in the coating layer of the sodium supplement is 0.5%.
[0096] Example 8
[0097] This embodiment provides a sodium supplement agent with the same system as that in Embodiment 1. The difference between this embodiment and Embodiment 1 is that the metal atoms loaded in the coating layer of the sodium supplement agent are Co, and the non-metal atoms doped in the coating layer are S. In step (1), by controlling the mass ratio of carbon material to sulfur powder, the mass content of N atoms in the coating layer of the sodium supplement agent is 1%. In step (2), by controlling the mass ratio of the first modified material to cobalt acetate, the mass content of Co atoms in the coating layer of the sodium supplement agent is 0.5%.
[0098] Example 9
[0099] This embodiment provides a sodium supplement agent with the same system as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass content of the core material in the sodium supplement agent is 80%, the mass content of the coating layer in the sodium supplement agent is 20%, and the metal atoms doped in the coating layer are Pd and Ni. In step (2), by controlling the mass ratio of the first modified material to the metal element raw materials palladium chloride and nickel acetate, the mass content of Pd atoms in the coating layer of the sodium supplement agent is 0.2%, and the mass content of Ni atoms is 0.5%.
[0100] Example 10
[0101] This embodiment provides a sodium supplement with the same system as that in Example 9. The difference between this embodiment and Example 9 is that the mass content of the core material in the sodium supplement is 85%, and the mass content of the coating layer in the sodium supplement is 15%.
[0102] Example 11
[0103] This embodiment provides a sodium supplement with the same system as in Example 9. The difference between this embodiment and Example 9 is that the mass content of the core material in the sodium supplement is 90%, the mass content of the coating layer in the sodium supplement is 10%, and the non-metallic atoms doped in the coating layer are N and B. In step (1), by controlling the mass ratio of carbon material to non-metallic raw materials urea and boric acid, the mass content of N atoms in the coating layer of the sodium supplement is 6% and the mass content of B atoms is 3%.
[0104] Example 12
[0105] This embodiment provides a sodium supplement with the same system as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that the non-metallic atoms doped in the coating layer are N and P, and the metallic atoms doped in the coating layer are Pd and Fe. In step (1), by controlling the mass ratio of carbon material to non-metallic raw materials urea and red phosphorus, the mass content of N atoms in the coating layer of the sodium supplement is 6% and the mass content of P atoms is 2%. In step (2), by controlling the mass ratio of the first modified material to metallic raw materials palladium chloride and ferric acetate, the mass content of Pd atoms in the coating layer of the sodium supplement is 0.2% and the mass content of Fe atoms is 0.5%.
[0106] Example 13
[0107] This embodiment provides a sodium supplement with the same system as that in Example 11. The difference between this embodiment and Example 11 is that the core material is CH3COONa, the mass content of the core material in the sodium supplement is 96%, and the mass content of the coating layer in the sodium supplement is 4%.
[0108] Example 14
[0109] This embodiment provides a sodium supplement with the same system as that in Example 11. The difference between this embodiment and Example 11 is that the core material is Na2C2O4, the mass content of the core material in the sodium supplement is 98%, and the mass content of the coating layer in the sodium supplement is 2%.
[0110] Comparative Example 1
[0111] This comparative example provides a sodium supplement agent, which is Na2CO3 without a carbon coating layer.
[0112] Comparative Example 2
[0113] This comparative example provides a sodium supplement, which is CH3COONa without a carbon coating.
[0114] Comparative Example 3
[0115] This comparative example provides a sodium supplement agent, which is Na2C2O4 without a carbon coating layer.
[0116] Comparative Example 4
[0117] This comparative example provides a sodium supplement comprising a core and a coating layer. The core material is Na2CO3, and the coating layer material is La2O3. The mass content of the core material in the sodium supplement is 90%, and the mass content of the coating layer in the sodium supplement is 10%.
[0118] Comparative Example 5
[0119] This comparative example provides a sodium supplement comprising a core and a coating layer. The core material is Na2CO3, and the coating layer material is Al2O3. The mass content of the core material in the sodium supplement is 90%, and the mass content of the coating layer in the sodium supplement is 10%.
[0120] Comparative Example 6
[0121] This comparative example provides a sodium supplement comprising a core and a coating layer. The core material is Na2C2O4, the coating layer material is Ni, the mass content of the core material in the sodium supplement is 98%, and the mass content of the coating layer in the sodium supplement is 2%.
[0122] Comparative Example 7
[0123] This comparative example provides a sodium supplement with the same system as in Example 1. The difference between this comparative example and Example 1 is that the coating layer of the sodium supplement does not contain metal atoms.
[0124] Comparative Example 8
[0125] This comparative example provides a sodium supplement with the same system as Example 11. The difference between this comparative example and Example 11 is that the coating layer of the sodium supplement does not contain non-metallic atoms.
[0126] The sodium supplements prepared in Examples 1 to 14 and Comparative Examples 1 to 8 were subjected to decomposition potential and specific capacity tests. The sodium supplements prepared in Examples 1 to 14 and Comparative Examples 1 to 8 were assembled into sodium-ion batteries, and the assembled batteries were subjected to storage gas generation tests to verify the efficacy of the present invention. The test results are shown in Table 1.
[0127] Sodium supplement capacity and decomposition potential test: The sodium supplement prepared above was mixed with conductive agent Super P and binder polyvinylidene fluoride (PVDF) in a weight ratio of 90:5:5. N-methylpyrrolidone (NMP) solvent was added and the mixture was stirred thoroughly to obtain a positive electrode slurry. The positive electrode slurry was coated onto the positive electrode current collector aluminum foil and prepared by drying, cold pressing and slitting. Sodium metal was used as the negative electrode and assembled in the following order: positive electrode shell - electrode sheet - electrolyte - separator - electrolyte - sodium sheet - gasket - spring sheet - negative electrode shell. The battery was then sealed using a sealing machine to obtain a CR2032 button half cell.
[0128] At 25°C, the coin cell was charged to 4.25V with a constant current of 1mA, and the initial charge capacity and initial charge energy of the coin cell were measured. The initial charge capacity of the sodium supplement was obtained by dividing the initial charge capacity by the mass of the sodium supplement. The decomposition potential of the sodium supplement was obtained by dividing the initial charge energy by the initial charge capacity.
[0129] The preparation process of sodium-ion batteries is as follows: The positive electrode material NFPP, a composite material containing sodium supplement (2% by mass), a positive electrode conductive agent, and a positive electrode binder are mixed at a weight ratio of 95:2.5:2.5. N-methylpyrrolidone (NMP) solvent is added, and the mixture is stirred under vacuum until homogeneous. The slurry solid content is adjusted to 55% to obtain the positive electrode slurry. The positive electrode slurry is coated onto carbon aluminum foil, dried, and cold-pressed to form the positive electrode sheet. The negative electrode material hard carbon, the negative electrode conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose (CMC-Na), and the negative electrode binder styrene-butadiene rubber (SBR) are mixed at a mass ratio of 96.6:0.8:1.2:1.4. Deionized water is added, and the slurry solid content is adjusted to 55%. The mixture is then thoroughly stirred under vacuum to obtain the negative electrode slurry. The negative electrode slurry is uniformly coated onto the negative electrode current collector copper foil, dried, and cold-pressed to form the negative electrode sheet. Using a 12μm thick porous PP membrane as the separator, the prepared positive electrode, separator, and negative electrode were stacked sequentially, with the separator positioned between the positive and negative electrodes to provide isolation. Then, an aluminum-plastic film was wrapped around the separator, and the mixture was dried in a vacuum oven at 120 °C. After injecting 5.0 g / Ah of electrolyte, the mixture was sealed. Following processes such as settling, hot and cold pressing, formation, clamping, and capacity testing, a 1 Ah soft-pack sodium-ion battery was finally obtained.
[0130] Sodium-ion battery gas production test: The prepared sodium-ion battery is placed in the test equipment, the equipment temperature is set to 25℃, and it is charged at a constant current and constant voltage of 0.33C to Vmax (Vmax is 4V). After full charging, the initial volume V1 of the battery is measured. Then the sodium-ion battery is placed in a hot box at 60℃, and the volume change is measured every 30 days (using the "water displacement method"). The volume V2 of the battery taken out on the 60th day is recorded, and the gas production growth of the battery can be obtained as (V2-V1) / V1.
[0131] Table 1: Sodium supplementation parameters and assembled battery performance test results provided in Examples 1 to 14 and Comparative Examples 1 to 8
[0132]
[0133] Comparing the test results of Examples 1 to 14 and Comparative Examples 1 to 3, it can be seen that by coating the core of the sodium-supplementing material with a carbon coating layer containing metal atoms and non-metal atoms, the decomposition potential of the sodium-supplementing agent can be effectively reduced, and the sodium-supplementing efficiency of the sodium-supplementing agent can be improved; and the gas generated when the core material decomposes can be effectively adsorbed, reducing the gas generation during high-temperature storage of sodium-ion batteries and effectively improving the cycle life of sodium-ion batteries.
[0134] Comparing the test results of Examples 1, 14 and Comparative Examples 4 to 6, it can be seen that, compared with sodium replenishing agent materials coated with metal oxides or metals on the outside, the sodium replenishing agent provided in this application utilizes the higher catalytic efficiency and stronger molecular adsorption performance of metal atoms and non-metal atoms in the coating layer to further reduce the decomposition potential of the sodium replenishing agent and suppress the decomposition gas production of the sodium replenishing agent, thereby avoiding the negative impact of the introduction of the sodium replenishing agent on the electrochemical stability of the battery, and thus effectively improving the charge and discharge capacity and cycle life of sodium-ion batteries equipped with sodium replenishing agents.
[0135] Comparing the test results of Example 1 and Comparative Example 7, it can be seen that the sodium supplement agent in the coating layer of the comparative example does not have metal atoms loaded in it. The sodium supplement agent provided in this application embodiment can improve the conductivity of the sodium supplement agent by utilizing the synergistic effect of metal atoms and non-metal atoms in the coating layer, reduce the decomposition potential of the sodium supplement agent, and increase the initial charge capacity of the sodium supplement agent; and efficiently absorb the gas released by the decomposition of the core material, further reducing the gas production of the sodium supplement agent.
[0136] The wetting properties of the sodium supplements provided in Example 11 and Comparative Example 8 were tested. Specifically, the sodium supplement and PVDF were mixed evenly at a mass ratio of 9:1, and then stirred in NMP to form a mixed slurry with a solid content of 50%. The mixed slurry was evenly coated onto a foil, with the coating thickness controlled at 150 μm. After drying, it was cut into electrode strips 250 mm long and 20 mm wide. The electrode strips were fixed in the grooves at the upper and lower ends of a separator, ensuring that the sample was straight without bending. The separator with the sample strips fixed was then slowly placed into a housing (which had been pre-filled with electrolyte, with the liquid level slightly lower than the height of the housing). Each groove on the separator had a graduation line (0.5 mm). The height of the electrolyte climbing up the electrode strip was recorded at regular intervals. By calculating the ratio of height to time, the electrolyte climbing speed could be obtained to compare the wetting effect of the sodium supplements provided in Example 11 and Comparative Example 8 in the electrolyte. The above tests showed that the climbing speed of the sodium supplement wetting electrolyte provided in Example 11 was 5 mm / min, and the climbing speed of the sodium supplement wetting electrolyte provided in Comparative Example 8 was 3.7 mm / min. It can be seen that by doping non-metallic elements in the coating layer, the wetting effect of the sodium supplement surface on the electrolyte can be effectively improved, the ion exchange rate between the sodium supplement and the electrolyte can be increased, and thus the charging capacity of the sodium supplement can be increased.
[0137] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A sodium supplement, characterized in that, include: The core includes a sodium-supplementing material, which includes at least one of Na2CO3, Na2NiO2, NaCrO2, Na2S, CH3COONa, Na2C4O4, and Na2C2O4. A coating layer comprising carbon material, metal atoms, and non-metal atoms, wherein the metal atoms and non-metal atoms are located within the carbon material; the carbon material comprises at least one of graphene, carbon nanotubes, hard carbon, soft carbon, carbon fiber, and conductive carbon. The core in the sodium supplement contains 85% to 96% by mass, the coating layer in the sodium supplement contains 4% to 15% by mass, the metal atoms in the coating layer contain 0.1% to 1% by mass, and the non-metal atoms in the coating layer contain 4% to 15% by mass. Wherein, the non-metallic atoms include at least one of N, B, S, and P; the metallic atoms include at least one of noble metal atoms and transition metal atoms, wherein the noble metal atoms include at least one of Ir, Rh, Ru, and Pd, and the transition metal atoms include at least one of Ni, Co, Mn, and Fe.
2. The sodium supplement according to claim 1, characterized in that, At least some of the non-metallic atoms are doped on the surface of the carbon material, and the metallic atoms are loaded in the carbon material.
3. The sodium supplement according to claim 2, characterized in that, The non-metallic atoms form hydrophilic groups on the surface of the carbon material.
4. A method for preparing the sodium supplement according to any one of claims 1 to 3, characterized in that, include: The first modified material is obtained by mixing and sintering carbon materials with non-metallic element raw materials. The first modified material is a carbon material doped with non-metallic atoms; The metal element raw material is mixed with the first modified material and sintered to obtain the second modified material; the second modified material is the first modified material loaded with metal atoms; The sodium-supplementing material is mixed and ground with the second modified material to obtain a sodium-supplementing agent.
5. A sodium-ion battery, characterized in that, The invention includes a positive electrode sheet, which comprises a positive current collector and a positive active material layer, wherein the positive active material layer comprises the sodium supplement agent as described in any one of claims 1 to 3, or the sodium supplement agent prepared by the preparation method described in claim 4.
6. An electronic device, characterized in that, The electronic device includes the sodium-ion battery of claim 5.
Citation Information
Patent Citations
Sodium-ion battery anode sodium supplement additive, sodium-ion battery anode pole piece and sodium-ion battery
CN110690437A
Preparation method of polyanionic sodium ion battery positive electrode material
CN116314795A